Un aporte de Edith Stein a la antropología de su tiempo: la empatía - Taubenschlag, Carlos Alfredo (Sapientia, 2020)
This paper aims at showing insight into the beginnings of the theory of empathy in Edith Stein, not only from a theoretical conceptualization, but also from the mere imitation of Stein's methodology, by briefly providing the readers with the initial steps to take, like in a workshop, to ease their encounter with another concept of empathy, and from then on, move onto the historical and cultural background that gave rise to Stein’s writings, providing specific and biographical data in order to fully familiarize with the style of the philosopher.